Cancer incidence and chemotherapy-induced adverse effects in Asia - Khatab, Nasir Ibrahim Omar; Sani, Dahiru; Kirby, Brian P.; Mohtarrudin, Norhafizah; Ho, Gwo Fuang; Basri, Hamidon; Stanslas, Johnson (International Islamic University Malaysia Press, 2019)
Objective: Primary care givers and researchers are challenged every day in finding an appropriate treatment for cancer. Chemotherapy is one of the treatments to treat cancer, however, the adverse effects from chemotherapy present a significant problem. The aim of this review is to present current standings of the incidence of cancer and the adverse effects from chemotherapy among Asians. Method: Studies which were conducted from 1990 through June 2018 containing phrases such as ‘Cancer incidence in Asia’, ‘chemotherapy-induced adverse effects in Asia’, ‘CIPN in Asia’, ‘CINV in Asia’ and ‘chemotherapy-induced anaemia in Asia’ were searched through PubMed, Google scholar and Scopus. Where appropriate, ‘Asia’ was replaced by the name of a specific country to ensure searching of the database. Results: Incident rates of new cancer cases and death in Asia are increasing which are estimated to reach 48 % of new cases and 55 % of death. While studies had reported using different chemotherapeutic agents to treat cancer, most of them detailed the adverse effects from chemotherapy that affected the patients, thus affecting their quality of life. Conclusion: Findings from this review concluded that cancer incident is increasing which may requires early detection of cancer and optimal treatment. This may aid in the selection of an appropriate chemotherapy regimen with reduced side effects.